2022
DOI: 10.35445/alishlah.v14i2.1350
|View full text |Cite
|
Sign up to set email alerts
|

Development of Lecturer Performance Assessment Instruments through the Plomp Model in Higher Education

Abstract: This study aims to examine the process of developing performance appraisal instruments and descriptions by referring to the lecturers of the Mathematics Tadris Study Program IAIN Palopo and analyzing their responses. This type of investigation uses research and development (Research and Development). Four phases follow it in the Plomp development model: the first phase, which is investigation-based; then there is the design phase; then there is the realization phase; then there are the test and evaluation phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The research subjects were students in class V of State Elementary School 02 and Indarung State Elementary School 07 and teachers of class V who were enrolled in the 2022-2023 school year. This development research uses the Plomp model (Nieveen et al, 2007;Thalhah et al, 2022;Rahmadani et al, 2022). The research model used is the Plomp model which is divided into 3 phases, namely the preliminary research phase, the development or prototyping phase, and the assessment phase as shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…The research subjects were students in class V of State Elementary School 02 and Indarung State Elementary School 07 and teachers of class V who were enrolled in the 2022-2023 school year. This development research uses the Plomp model (Nieveen et al, 2007;Thalhah et al, 2022;Rahmadani et al, 2022). The research model used is the Plomp model which is divided into 3 phases, namely the preliminary research phase, the development or prototyping phase, and the assessment phase as shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to most other instructional content, online assessment has become a useful component of learners' language skills development. Language proficiency is a key aspect in learning and teaching that teachers must promote [8]. The criticality of language skills for real-life situations, such as in job applications, should cause teachers to test students on language competence and knowledge.…”
Section: Online Assessment 31 Online Summative Assessment Tasksmentioning
confidence: 99%
“…The criticality of language skills for real-life situations, such as in job applications, should cause teachers to test students on language competence and knowledge. Indeed, language proficiency assessment can lead to succinct and clear statements of individual learner competency in language, and it is more personal [8]. In other words, when using this type of assessment, teachers must ensure that they are considering individual differences among students in the assessment design.…”
Section: Online Assessment 31 Online Summative Assessment Tasksmentioning
confidence: 99%
“…3) Small Group Test After conducting a one-to-one evaluation and the product has been revised, the next step is product testing through a small group test [26]. In this case, product trials were carried out to students of class XI MIA SMAN Mapat Tunggul Selatan.…”
Section: ) One To One Evaluationmentioning
confidence: 99%